Survival study and prognostic factors of ovarian cancer registered in a teaching hospital in Malaysia - Najihah Lokman,; Siti Azrin Ab. Hamid,; Norsa’adah Bachok, (Penerbit Universiti Kebangsaan Malaysia, 2017)
Ovarian cancer is one of the highest causes of death among female population in Malaysia. A retrospective cohort study among 127 ovarian cancer patients registered in one of the teaching hospital in Malaysia was conducted from 1st January 2002 until 31st December 2011. The objective of this study was to determine the median survival time, five year survival probability and prognostic factors of ovarian cancer patients. Only ovarian cancer patients were selected with strict inclusion and exclusion criteria. Data was analyzed using Kaplan-Meier Survival analysis and Cox proportional hazard regression analysis. The results showed that the overall five-year survival probability of ovarian cancer was 35.2% (95%CI: 26.3, 44.3) with 38 month (95%CI: 25.7, 50.1) median survival time. After adjustment for potential cofounder, significant prognostic factors of ovarian cancer were observed in FIGO stage (HR: 2.53; 1.44, 4.45), loss of appetite (HR: 1.95; 1.23, 3.11) and presence of pleural effusion (HR: 1.98; 1.19, 3.30). Overall, the survival probabilities of ovarian cancer were low and further actions must be taken to improve the survival among advanced cancer patients